Evaluating the challenges of implementing social value in the procurement of construction works - Brandsford Kwame Gidigah; Kofi Agyekum; Bernard Kofi Baiden (Journal of Responsible Production and Consumption)
Purpose – There is proliferation of regulatory frameworks and guidelines globally to implement social considerations in the procurement of construction projects. However, there are scanty empirical studies that have researched into the implementation of social consideration in the procurement of construction projects in Africa, particularly Ghana. Therefore, this study aims to examine the challenges that hinder the implementation of social value in the procurement of construction works in Ghana. Design/methodology/approach – The study used an explanatory sequential mixed-methods design with an initial quantitative instrument phase, followed by a qualitative data collection phase. A critical comparative review of the related literature resulted in the identification of 29 challenges. A total of 100 questionnaire responses from professionals in the construction industry in Ghana based on the challenges on the implementation of social value were retrieved. The data obtained were coded with SPSS version 22, analysed descriptively (mean scores and standard deviation) and via inferential analysis (exploratory factor analysis). These data were then validated through semi-structured interviews with 10 professionals. The data obtained from the semi-structured validation interviews were analysed through the side-by-side comparison of the qualitative data with the quantitative data. Findings – The results revealed that the critical challenges to the implementation of social value in the procurement of construction works can be clustered into three major components, i.e. weak processes and bureaucracy, the incongruence of social value with the traditional procurement process, and the misaligned social targets and erosion of public procurement principles. The interviewees agreed to and confirmed the criticality of these factors as challenges to the implementation of social value in the procurement of construction works. Research limitations/implications – A substantial number of studies have identified numerous challenges to the implementation of social value. This study presents a major cluster of challenges to the implementation of social value. Social value through construction procurement is a strategic tool globally and Ghana can leverage on its multiplier effects for social development. Originality/value – The study extends the global discourse on social value in construction management literature by providing empirical evidence on the cluster of challenges that have the potential to hinder the implementation of social value in the procurement of construction works.